UPLC-Q-TOF/MS-Based Serum and Urine Metabonomics Study on the Ameliorative Effects of Palmatine on Helicobacter pylori–Induced Chronic Atrophic Gastritis - Chen, Xing; Zhang, Jianzhong; Wang, Ruilin; Liu, Honghong; Bao, Chunmei; Wu, Shihua; Wen, Jianxia; Yang, Tao; Wei, Ying; Ren, Sichen; Tong, Yuling; Zhao, Yanling (Frontiers in Pharmacology, 2020)
Objective The main objective of this study was to investigate the ameliorative effects of Palmatine (Pal) on Helicobacter pylori (H. pylori) induced chronic atrophic gastritis (CAG) Method Body function, serum biochemical indicators and histopathology were used to evaluate the pharmacodynamics of Pal on CAG rats. The target genes expression levels were verified and assessed by RT-PCR and immunohistochemistry. Moreover, UPLC-Q-TOF / MS analysis based on urine and serum was performed to identify the potential metabolites in the pathological process of CAG induced by H. pylori. Metabolic pathway analysis was performed to elucidate the metabolic network associated with Pal treatment of CAG. Results Pal (10, 20, 40 mg / kg / d) significantly restored the body function of CAG rats, reduced the serum biochemical indicators, and maintained the integrity of the gastric mucosal epithelial barrier while alleviated gastric histological damage. Metabolomics analysis shows that the therapeutic effect of Pal on CAG involves 10 metabolites and 10 metabolic pathways, of which the Taurine and hypotaurine metabolism, Glycerophospholipid metabolism and Pentose and glucuronate interconversions are closely related to the gastrointestinal protection of Pal, and these metabolic pathways crosstalk with each other due to the internect hub of citric acid cycle. Conclusions Metabolomics was used for the first time to identify potential biomarkers of CAG and to illuminate the therapeutic mechanism of Pal on CAG induced by H. pylori. The results provided a new insights for further research on CAG treatment.